Survei Indeks Massa Tubuh Dan Tingkat Daya Tahan Kardiovaskular (VO2MAX) Peserta Ekstrakurikuler Olahraga Sekolah Menengah Atas - Anwarul Fadli; Hariyoko Hariyoko (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Body mass index is used to indicate the proportional category of a person's weight. A person's body mass index more or less also affects cardiovascular endurance (VO2MAX). One way to improve cardiovascular endurance in school is through extracurricular activities. Extracurricular is a forum for personal development of students through various activities both directly and indirectly. The purpose of this study was to determine and examine the body mass index and cardiovascular endurance level (VO2MAX) of extracurricular sports participants at SMAN 1 Bululawang. In this study, researchers used quantitative descriptive research with survey methods and cross sectional approaches. The subjects of this study were 40 extracurricular sports participants at SMAN 1 Bululawang. From the results of research conducted on sports extracurricular participants at SMAN 1 Bululawang, it can be concluded that the results of the body mass index are included in the ideal weight category and the level of cardiovascular endurance (VO2Max) is included in the very low criteria.